Dominant vs. non-dominant shoulder and elbow range-of-motion differences in softball pitchers - McDonald, L. M.; Kaminski, T. W.; Werner, S. L. (Journal of Athletic Training, 2013)
Shoulder and elbow range-of-motion in softball pitchers are not well documented. Side-to-side comparisons of baseball pitchers have demonstrated glenohumeral internal rotation deficits (GIRD) with concurrent increases in external rotation, as well as changes at the elbow. Rehabilitative strategies are typically implemented to prevent related pathology in these athletes. Despite softball pitchers delivering the ball underhand, range-of-motion differences may exist that can drive preventative or rehabilitative treatment decisions for clinicians. Objective: Compare dominant and non-dominant passive range of motion (PROM) for shoulder internal rotation (SIR), shoulder external rotation (SER), elbow extension (EEX), and elbow carrying angle (ECA) in softball pitchers. We hypothesized no differences between sides. Design: Within-subjects comparison. Setting: Climate-controlled biomechanics laboratory. Patients or Other Participants: Forty-three female softball pitchers (17.2±2.1 yrs.; 164.7±6.7 cm; 65.6±11.4 kg) were recruited to participate. All subjects were injury free at time of collection. Two pitchers were left-handed. Interventions: PROM was assessed using a standard goniometer. SER and SIR were measured supine with the humerus abducted to 90° and the elbow flexed 90°. Start position (0°) was defined as the forearm perpendicular to the table. For both measurements, the humerus was moved passively to the subject`s end range-of-motion. End range was determined when the subject`s scapula began to aid humeral motion or a firm end-feel was achieved. For EEX, the goniometer was placed with the axis at the lateral epicondyle as the elbow was moved to the subject`s extension end range-of-motion. ECA was measured with the subject standing, arms relaxed at side, and axis of the goniometer at the cubital fossa. Main Outcome Measures: Three trials were performed for each range-ofmotion and averaged to obtain a final value in degrees. Paired t-tests were conducted to compare dominant and non-dominant sides for each measurement. Results: At the shoulder, SER demonstrated significance (p<.001) between the dominant (84.5°±7.4°) and nondominant (78.9°±6.8°) shoulders. SIR was also significantly different (p=.012) between the dominant (71.3°±12.3°) and non-dominant (77.5°±8.9°) sides. At the elbow, ECA was significant (p=.002) between sides (dominant: 8.4°±2.5; non-dominant: 10.3°±2.8°). Conclusions: Though softball pitchers are not typically associated with the same pathologies that occur in baseball pitchers, these results suggest that side-to-side differences in shoulder and elbow range-of-motion exist. Unlike baseball, a softball pitcher may play other positions. Further research is necessary to determine if these rangeof- motion differences manifest as a result of underhand pitching or the overhand throwing necessary in field positions. Regardless of the source, it is important for clinicians to be cognizant of side-to-side range-ofmotion differences in softball pitchers and consider implementing injury prevention strategies as they would with a baseball pitcher.